Adenosine Receptor Modulates Permissiveness of Baculovirus (Budded Virus) Infection via Regulation of Energy Metabolism in Bombyx mori - Lin, Yu-Hsien; Tai, Chia-Chi; Brož, Václav; Tang, Cheng-Kang; Chen, Ping; Wu, Carol P.; Li, Cheng-Hsun; Wu, Yueh-Lung (Frontiers in Immunology, 2020)
Although the modulation of host physiology has been interpreted as an essential process supporting baculovirus propagation, the requirement of energy supply for host antivirus reactions could not be ruled out. Our present study showed that metabolic induction upon AcMNPV (budded virus) infection of Bombyx mori stimulated virus clearance and production of the antivirus protein, gloverin. In addition, we demonstrated that adenosine receptor signaling (AdoR) played an important role in regulating such metabolic reprogramming upon baculovirus infection. By using a second lepidopteran model, Spodoptera frugiperda Sf-21 cells, we demonstrated that the glycolytic induction regulated by adenosine signaling was a conservative mechanism modulating the permissiveness of baculovirus infection. Another interesting finding in our present study is that both BmNPV and AcMNPV infection cause metabolic activation, but it appears that BmNPV infection moderates the level of ATP production, which is in contrast to a dramatic increase upon AcMNPV infection. We identified potential AdoR miRNAs induced by BmNPV infection and concluded that BmNPV may attempt to minimize metabolic activation by suppressing adenosine signaling and further decreasing the host’s anti-baculovirus response. Our present study shows that activation of energy synthesis by adenosine signaling upon baculovirus infection is a host physiological response that is essential for supporting the innate immune response against infection.